Analysis of the policies and collection procedures of salary loan of SSS branch office in España, Manila - Gonzaga, Kristiann Loyd Micua (Manila : National University, 2004)
This analysis aroused the importance of having an overview of what our government services are. Through this analysis, we know our privilege such as the salary loan.
Chapter 1 : Introduction and its Background -- Chapter 2 : Review of Related Literature -- Chapter 3 : Research and Methodology -- Chapter 4 : Presentation, Interpretation and Analysis of Data -- Chapter 5 : Summary, Conclusion and Recommendation -- Bibliography -- Appendices
Includes bibliographical references.